Japan's priorities in Taiwan: Its impacts on Japanese relations with America and China - Sahibzada Muhammad Usman (IDEA PUBLISHERS, 2021)
America-Japan partnership is now at the core of the America-led defence system in the East Asia. The unresolved state of Taiwan is already one of the worst security conditions in the region in the terms of this partnership. It may contribute to a big confrontation of one or both countries with China. The broader Taiwan-Japan-China-America ties usually regard Taiwan and Japan as the least influential combination imaginable. Despite this fact, the depth of engagement, hard to categorize and with great potential to affect stability and security in the field, is reversed from this tertiary regional connection. Therefore, Japan's major goal to balance the power with Taiwan is to preserve and develop constructive de-facto state-to-state ties between the liberal and democratic powers of similar consciousness, both of which are scared of the Chinese control. This paper discusses the specific ties between Japan and Taiwan in conjunction with Japanese domestic priorities and analyses the repercussions for America-Japan cooperation in the future. Especially about Japan, the American and Taiwanese governments should identify areas of difference early on and resolve emerging issues within the alliance's auspices.